A Grid-Based Coulomb Collision Model for PIC Codes - Jones, Michael E.; Lemons, Don S.; Mason, Rodney J.; Thomas, Vincent A.; Winske, Dan (Journal of computational physics, 1996)
A new method is presented to model the intermediate regime between collisionless and Coulomb collision dominated plasmas in particle-in-cell codes. Collisional processes between particles of different species are treated through the concept of a grid-based “collision field,” which can be particularly efficient for multi-dimensional applications. In this method, particles are scattered using a force which is determined from the moments of the distribution functions accumulated on the grid. The form of the force is such to reproduce the multi-fluid transport equations through the second (energy) moment. Collisions between particles of the same species require a separate treatment. For this, a Monte Carlo-like scattering method based on the Langevin equation is used. The details of both methods are presented, and their implementation in a new hybrid (particle ion, massless fluid electron) algorithm is described. Aspects of the collision model are illustrated through several one- and two-dimensional test problems as well as examples involving laser produced colliding plasmas.